Effectiveness Of Minimum Competency Assessment (Akm) Questions For Reading Literacy On Short Story Text Materials For Grade Viii Smp Using Google Forms - Kusdiana Sari, Febi; Zisca Diana, Purwati (International Proceedings of Nusantara Raya, 2024)
This research aims to develop effective minimum competency assessment (AKM) questions to enhance students' understanding of short story texts. AKM is an educational evaluation tool in Indonesia designed to ensure that students' basic competencies meet knowledge and comprehension standards, especially in reading literacy. The method used in this study is Research and Development (R&D) with the ADDIE approach, which includes analysis, design, development, implementation, and evaluation. The results indicate that: (1) needs analysis reveals that students still lack understanding of AKM questions; (2) there is a need to develop AKM questions using Google Form technology to make them more engaging and facilitate students' comprehension; (3) the developed AKM questions achieved an average score of 85, categorized as "very good" by experts. In conclusion, the developed product is proven effective in improving students' abilities and knowledge in understanding short story texts.